2020
DOI: 10.1016/j.colegn.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Double degree destinations: Nursing or midwifery

Abstract: Background: Double degrees in nursing and midwifery have evolved in Australia as a proposed solution to possible impending shortages of qualified midwives in the healthcare workforce. The double degree is seen as a more acceptable option in non-metropolitan areas in particular. Concern has been expressed however, about dilution of midwifery philosophy and graduates' opportunities in respect of future clinical practice. Aim: This study aimed to provide a better understanding of motivations and intentions of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Much has been done in Australian law and professional bodies to recognise midwifery as a profession in its own right. [47] However, there remains concern that midwives are underrepresented on key government committees, advisory groups, and expert panels, with a need for more equitable representation on decision-making committees. [8] A lack of midwifery-specific education and workforce data also remained challenging.…”
Section: Government Policy and Legislation Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been done in Australian law and professional bodies to recognise midwifery as a profession in its own right. [47] However, there remains concern that midwives are underrepresented on key government committees, advisory groups, and expert panels, with a need for more equitable representation on decision-making committees. [8] A lack of midwifery-specific education and workforce data also remained challenging.…”
Section: Government Policy and Legislation Reformmentioning
confidence: 99%
“…[49] This gave rise to support for double degrees, where students can complete the registration requirements for nursing and midwifery in a four-year degree, advocating that clinicians with both qualifications would be more suited to regional and rural areas. [47] Further arguments to support this combination of degrees included limited access to university in some regional areas of the country, a rise in co-morbidities in birthing women, and increased employability with dual registration. [47] However, there is limited research exploring or supporting this argument.…”
Section: Midwives For Rural Maternity Care and First Nation Communitiesmentioning
confidence: 99%
“…The most common ground for pursuing a double major is the career path and career growth. In fact, double major has successfully prepared students for work (Yates et al, 2020). In a study conducted by Zhu and Zhang, (2021) showed that 68 percent of students who chose a double major were being competitive in industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The International Confederation of Midwives (ICM) recognizes a midwife as: a person who has successfully completed a midwifery education programme that is based on the ICM Essential Competencies for Basic Midwifery Practice and the framework of the ICM Global Standards for Midwifery Education and is recognized in the country where it is located; who has acquired the requisite qualifications to be registered and/or legally licensed to practice midwifery and use the title 'midwife'; and who demonstrates competency in the practice of midwifery. (ICM 2017) Unlike nurses, midwives work predominantly in a framework underpinned by wellness, rather than illness (Nordby 2016(Nordby , 2017Yates et al 2020), and midwives have also existed throughout recorded history. They work with women throughout childbearing including: pregnancy, labor, childbirth, and the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Their scope of practice also extends across the lifespan of women incorporating sexual and reproductive health. Hence, they work under a framework of woman-centered care (McKenna 2009;Yates et al 2020). However, models of midwifery care vary around the world as education and practice have evolved locally.…”
Section: Introductionmentioning
confidence: 99%